Religious practices and Christianization of the late antique city (4th-7th century) - Busine, Aude. (Religions in the Graeco-Roman World, 2015)
In Religious Practices and Christianization of the Late Antique City , historians, archaeologists and historians of religion provide studies of the phenomenon of the Christianization of the Roman Empire within the context of the transformations and eventual decline of the Greco-Roman city. The eleven papers brought together here aim to describe the possible links between religious, but also political, economic and social mutations engendered by Christianity and the evolution of the antique city. Combining a multiplicity of sources and analytical approaches, this book seeks to measure the impact on the city of the progressive abandonment of traditional cults to the advantage of new Christian religious practices.